2016
DOI: 10.1155/2016/1980763
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Downregulates Phosphate Carrier and Protects against Doxorubicin Induced Cardiomyocyte Apoptosis

Abstract: Aim. To explore the effects of curcumin on phosphate carrier (PiC) and its role in protection against doxorubicin induced myocyte toxicity. Methods. Using H9c2 cell line, the cardiotoxic effect of doxorubicin and its mitigation by curcumin were studied. H9c2 cells were cultured with doxorubicin and/or curcumin at various concentrations. Analysis for apoptosis of H9c2 was done using flow cytometry. Confocal laser scanning microscopy was used to record the fluorescence intensity ratios and to determine the mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Multiple reports have demonstrated that doxorubicin-induced cardiac toxicity is decreased by anti-apoptotic methods in various animal models. [26][27][28] It is known that ursolic acid protects the heart from ischaemic reperfusion injury or infarction by anti-apoptotic activities. [29][30][31] Therefore, via anti-apoptosis, ursolic acid may decrease the side effects of doxorubicin on the heart.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple reports have demonstrated that doxorubicin-induced cardiac toxicity is decreased by anti-apoptotic methods in various animal models. [26][27][28] It is known that ursolic acid protects the heart from ischaemic reperfusion injury or infarction by anti-apoptotic activities. [29][30][31] Therefore, via anti-apoptosis, ursolic acid may decrease the side effects of doxorubicin on the heart.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the strategy against the mitochondrial pathway of apoptosis is reasonable in preventing the cardiac toxicity caused by doxorubicin. Reportedly, the cardiac toxicity caused by doxorubicin is decreased in various animal models by the antiapoptotic methods [ 26 28 ]. Several studies showed that Rg1 protects the heart from ischemic reperfusion injury or heart infarction by the effect of anti-apoptosis [ 17 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that curcumin could protect against Dox-induced cardiotoxicity. The key mechanisms postulated for the cardioprotective activity of curcumin include induction of apoptosis, JNK activation, abrogation of inflammation, and excessive opening of mitochondrial permeability transition pores [ 35 , 36 , 37 , 38 , 39 , 40 ]. Therefore, pre-treatment with curcumin could be considered in cancer chemotherapeutic applications.…”
Section: Small Molecules That Attenuate Dox-induced Cardiotoxicitymentioning
confidence: 99%